Characteristics and outcomes of five patients with COVID‐19 and hematological malignancies. Issue 6 (10th June 2021) - Citterio, Chiara; Lazzaro, Antonio; Bosi, Costanza; De Ponzio, Maurice; Cavanna, Luigi
Abstract: Patients with hematological cancer are at major risk of developing infectious complication. The prevention and treatment of COVID‐19 in these patients is challenging. This experience, with the limitation of a small number of patients, highlights that early treatment of COVID‐19 can overcome the infection, also in hematological patients. Abstract : Patients with hematological cancer are at major risk of developing infectious complication. The prevention and treatment of COVID‐19 in these patients is challenging. This experience, with the limitation of a small number of patients, highlights that early treatment of COVID‐19 can overcome the infection, also in hematological patients.